Of activists and gatekeepers: temporal and structural properties of policy networks on Twitter - Stier, Sebastian; Schünemann, Wolf J.; Steiger, Stefan (New media & society, 2017)
There is an ongoing academic debate whether social media empowers activists and advocacy groups in relation to established political actors and media gatekeepers. This article investigates these premises by analysing the influence of various actors in two policy debates on Twitter, environmental policy (climate change) and Internet governance (net neutrality). We extract tweets on both topics and code the respective 500 most central accounts according to a categorisation of relevant political actor groups. Applying methods from social network analysis, we reveal temporally fluctuating actor constellations and network structures which converge to elite actors during high attention periods. Furthermore, a comparative keyword analysis shows that non-governmental organisations and citizen media emphasise personalised connective action frames, whereas political actors and traditional media tend to refer to the political decision-making process and its institutions. Both findings are in line with cyclical conceptions of policy processes.
First published June 27, 2017
Gesehen am 15.04.2020